The Risks of Revolution: Ethical Dilemmas in 3D Printing from a US Perspective. - Neely, Erica (Science & Engineering Ethics, 2016)
Additive manufacturing has spread widely over the past decade, especially with the availability of home 3D printers. In the future, many items may be manufactured at home, which raises two ethical issues. First, there are questions of safety. Our current safety regulations depend on centralized manufacturing assumptions; they will be difficult to enforce on this new model of manufacturing. Using current US law as an example, I argue that consumers are not capable of fully assessing all relevant risks and thus continue to require protection; any regulation will likely apply to plans, however, not physical objects. Second, there are intellectual property issues. In combination with a 3D scanner, it is now possible to scan items and print copies; many items are not protected from this by current intellectual property laws. I argue that these laws are ethically sufficient. Patent exists to protect what is innovative; the rest is properly not protected. Intellectual property rests on the notion of creativity, but what counts as creative changes with the rise of new technologies.